Analisis Budaya Organisasi dan Motivasi Kerja serta Pengaruh terhadap Kinerja Tenaga Kependidikan - Rifaldi Permana; R.M Juddy Prabowo (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the influence of organizational culture and work motivation on the performance of educational staff, both simultaneously and partially. This type of research is quantitative, with 44 respondents for variables X1, descriptive, and associative, with the SPSS version 26 program as a data processing tool. This research shows that organizational culture and work motivation simultaneously influence the performance of the Assakinah Sejahtera Foundation education staff at West Bandung Regency. Then, organizational culture does not affect the performance of education staff, and work motivation has a positive effect on the performance of education staff. In conclusion, the performance assessment shows a decline in the Assakinah Sejahtera Foundation Education Personnel, West Bandung Regency. Keywords: Organizational Culture, Work Motivation, Performance